2020
DOI: 10.1002/jcph.1713
|View full text |Cite
|
Sign up to set email alerts
|

A Physiological Approach to Pharmacokinetics in Chronic Kidney Disease

Abstract: The conventional approach to approximating the pharmacokinetics of drugs in patients with chronic kidney disease (CKD) only accounts for changes in the estimated glomerular filtration rate. However, CKD is a systemic and multifaceted disease that alters many body systems. Therefore, the objective of this exercise was to develop and evaluate a whole-body mechanistic approach to predicting pharmacokinetics in patients with CKD. Physiologically based pharmacokinetic models were developed in PK-Sim v8.0 (www.open-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 88 publications
0
35
0
Order By: Relevance
“…adefovir, oseltamivir carboxylate [ 23 , 62 ]), with also some reports for substrates for OCT2/MATEs (e.g. metformin, atenolol, creatinine [ 26 , 46 , 63 ]) and OATP4C1/ P-gp (e.g. digoxin [ 14 ]).…”
Section: Discussionmentioning
confidence: 99%
“…adefovir, oseltamivir carboxylate [ 23 , 62 ]), with also some reports for substrates for OCT2/MATEs (e.g. metformin, atenolol, creatinine [ 26 , 46 , 63 ]) and OATP4C1/ P-gp (e.g. digoxin [ 14 ]).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the C max and AUC 0-t of saxagliptin increased by less than 2-fold in patients with severe hepatic impairment but by more than 2-fold in patients with severe renal impairment, respectively ( Boulton, 2017 ). PK simulation in humans with hepatic or renal impairment is performed by modulating many physiological parameters based on healthy humans ( Malik et al, 2020 ). However, currently, this simulation model cannot simulate PK of patients with hepatic or renal impairment yet.…”
Section: Discussionmentioning
confidence: 99%
“…The final virtual healthy individual models were replaced with individuals whose parameter sets were adapted for renal impairment meanwhile the parameters of drug were left unchanged. The whole-body anatomy and physiology in patients throughout the progressive stages of CKD such as kidney volume fraction, renal perfusion fraction, fraction unbound in plasma, gastric emptying time and small intestinal transit time were changed according to literatures ( Malik et al, 2020 ). Changes in the physiological parameters, resulting from decreased renal function, were listed in Table 2 .…”
Section: Methodsmentioning
confidence: 99%